Desigualdades nas produtividades do trabalho no Brasil: uma avaliação usando a teoria do capital humano - Lima, Antônia Cleidiane Rocha (2017)
This study evaluated inequalities in productivity of the workforce in Brazil having as anchor the Human Capital Theory, which states that higher yields are associated with a healthier and qualified labor force. The data came from the Censuses of 2000 and 2010, provided by the IBGE (Brazilian Institute of Geography and Statistics). Observations units were the municipalities. To assess the preventive health, was built Sanitation Index (ISAN) through factor analysis method with decomposition main components. The education index was measured by the percentage of the population over 25 years concluded at least the Middle Level. With regard to productivity measure, it was considered the relationship between GDP (Gross Domestic Product) of each municipality and the population of 25 years or more. Thus, it was possible to estimate the impact of education and force of labor on labor productivity by means of contrasts analysis and also through econometric modeling. The results showed that the higher the level of access of the population to education, running water, sanitation and systematic garbage collection, the greater will be Labor Productivity. It was also observed that the higher elasticities found for both education and for ISAN are larger in the set of municipalities that are not part of semiarid zone comparatively to those included in this ecosystem. The survey also showed that in municipalities with the highest population rural/ urban population relations, the labor productivity tended to be smaller. This is because these municipalities estimated values for ISAN and the education index were also lower.